Central Nervous System Melanoma: Report of two cases - Karki, Prasanna; Shakya, Rupesh; Acharya, Shoshan Raj; Sharma, Apurva; Joshi, Sumit; Paudel, Prakash; Bikram Shah, Damber; Sharma, Gopal Raman (Nepal Journal of Neuroscience, 2023)
Primary brain melanomas are exceedingly rare, and metastasis outside of the central nervous system is an uncommon occurrence. The patients initially presented with an intraparenchymal hematoma with associated symptoms. Extensive diagnostic tests did not reveal any tumor-related or vascular patterns contributing to these bleedings. A comprehensive surgical resection was conducted, and the diagnosis of Central Nervous System (CNS) melanoma was confirmed through histological examination. Despite the generally poor prognosis associated with malignant melanomas, the combination of complete surgical resection and emerging therapies is extending overall survival and enhancing the quality of life. In cases where primary brain melanoma is suspected, even in the presence of extracerebral metastasis, aggressive treatment may be a viable consideration.